ANALISIS BEBAN PENCEMAR UDARA AMBIEN DARI KEGIATAN TRANSPORTASI DI RUAS JALAN SOEBRANTAS KOTA PEKANBARU - Siregar, Yusni Ikhwan (Jurnal Kajian Lingkungan, 2014)
Network for special road, especially in urban imbalance occurs between the growth rate of the road on one side with a growth rate of vehicles on the other, where the growth path is much smaller than the growth rate of the vehicle, this means showing the occurrence of an excessive load on the road. These conditions resulted in traffic congestion, disrupted travel convenience, travel fatigue, boredom trips, increased air pollution, wastage of time and material it also occurs on roads Soebrantas.The observation of the volume of vehicles on Sunday has the highest volume of 87.059 units 86.384 units followed Saturday and Sunday 73.125 units. The observation of Sunday vehicle top speed is 56,90 km/h followed Friday 54,57 km/h and Saturdays 50,26 km/h. Contributions load of pollutants CO are the largest contributor of pollutant loads. The total load of pollutants on Friday 5.265.420,06 grams/day consisting of CO: 92,43%, NOx: 6,32%, PM10: 1,0% and SO2: 0,25%. Total pollutant load Saturday 4.285.967,57 grams/day percentages: CO: 91,59%, NOx: 6,99%, PM10: 1,13% and SO2: 0,29%. The pollution load on the Sunday 5.215.978,35 grams/day percentages: CO: 92,29%, NOx: 6,41%, PM10: 1,04% and SO2: 0,26%.The main contribution of CO and NO2 pollutant load is predominantly gasoline fueled cars, the dominant source of PM10 motorcycle and SO2 pollutant load is the dominant truck. The results of ambient air quality monitoring for parameters of CO, NOx, PM10 and SO2 in Soebrantas streets on Friday to Sunday is still below the threshold value of ambient air quality.Keywords: Transportation, Motor Vehicles, Pollutant Load